The Effect of Alendronate on Osteoclastogenesis in Different Combinations of M-CSF and RANKL Growth Factors - Hedvičáková, Věra; Žižková, Radmila; Buzgo, Matěj; Rampichová, Michala; Filová, Eva (Biomolecules, 2021)
Bisphosphonates (BPs) are compounds resembling the pyrophosphate structure. BPs bind the mineral component of bones. During the bone resorption by osteoclasts, nitrogen-containing BPs are released and internalized, causing an inhibition of the mevalonate pathway. As a consequence, osteoclasts are unable to execute their function. Alendronate (ALN) is a bisphosphonate used to treat osteoporosis. Its administration could be associated with adverse effects. The purpose of this study is to evaluate four different ALN concentrations, ranging from 10-6 to 10-10 M, in the presence of different combinations of M-CSF and RANKL, to find out the effect of low ALN concentrations on osteoclastogenesis using rat and human peripheral blood mononuclear cells. The cytotoxic effect of ALN was evaluated based on metabolic activity and DNA concentration measurement. The alteration in osteoclastogenesis was assessed by the activity of carbonic anhydrase II (CA II), tartrate-resistant acid phosphatase staining, and actin ring formation. The ALN concentration of 10-6 M was cytotoxic. Low ALN concentrations of 10-8 and 10-10 M promoted proliferation, osteoclast-like cell formation, and CA II activity. The results indicated the induction of osteoclastogenesis with low ALN concentrations. However, when high doses of ALN were administered, their cytotoxic effect was demonstrated.
Keywords: RANKL; Rats; Actins; Leukocytes, Mononuclear; karboanhydrasa II; alendronate; DNA; osteoclastogenesis; leukocyty mononukleární; M-CSF; aktiny; Cell Proliferation; RANK Ligand; Carbonic Anhydrase II; krysa rodu Rattus; Osteogenesis; barvení a značení; osteogeneze; zvířata; Humans; Staining and Labeling; osteoklasty; ligand RANK; proliferace buněk; Tartrate-Resistant Acid Phosphatase; faktor stimulující kolonie makrofágů; Macrophage Colony-Stimulating Factor; alendronát; Alendronate; kyselá fosfatasa rezistentní k tartarátu; lidé; Osteoclasts; Animals